2014
DOI: 10.1111/bju.12331
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in men treated for testicular cancer

Abstract: Objective• To study the unique characteristics of erectile dysfunction (ED) in a population of men who developed ED after testicular cancer (TC) diagnosis and treatment. Patients and Methods• All men treated for TC who presented for sexual function evaluation were included in an institutional database.• All men underwent standard evaluation including a history/physical examination, completion of the International Index of Erectile Function (IIEF) questionnaire, testosterone/gonadotropin measurement and penile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…All patients had normal Doppler ultrasound, with 9 of 10 responding to Infertility with Testicular Cancer phosphodiesterase type 5 inhibitors; 1 in 4 had low testosterone (<300 ng/dL). 45 Overall, there are significant long-term psychological and sexual effects of testicular cancer treatment, regardless of the modality chosen, including surveillance.…”
Section: Psychological and Sexual Effects Of Cancermentioning
confidence: 99%
“…All patients had normal Doppler ultrasound, with 9 of 10 responding to Infertility with Testicular Cancer phosphodiesterase type 5 inhibitors; 1 in 4 had low testosterone (<300 ng/dL). 45 Overall, there are significant long-term psychological and sexual effects of testicular cancer treatment, regardless of the modality chosen, including surveillance.…”
Section: Psychological and Sexual Effects Of Cancermentioning
confidence: 99%
“…In addition, erectile dysfunction and other sexual disorders have been reported in patients who received different treatments (chemotherapy, radiotherapy and surgery) for testicular neoplasms and survived cancer. The aetiology remains unclear, as various organic, treatment‐related and psychogenic pathogenetic mechanisms have been proposed in the literature (Hartmann et al ., ; Nazareth et al ., ; Rosendal et al ., ; Eberhard et al ., ; Kim et al ., ; Tal et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A cross‐section of 76 patients with TC was evaluated in order to examine their hemodynamics with penile Doppler ultrasonography as an assessment of the organic factors and graded erectile function by using the International Index of Erectile Function (IIEF). The study concluded that the patients had normal erectile hemodynamics, which suggested that their ED could have been psychogenic . Another study reported that 25.5% of the 143 survivors of TC experienced ED after chemotherapy, RT, or RPLND and the median time to recovery was 60‐70 months, regardless of the modality, based on IIEF scores .…”
Section: Quality Of Life and Sexual Dysfunctionmentioning
confidence: 98%
“…78 One study reported a wide-range frequency of ED (12%-40%) in patients with TC and attributed it to organic or psychogenic etiologies. 79 A cross-section of 76 patients with TC was evaluated in order to examine their hemodynamics with penile Doppler ultrasonography as an assessment of the organic factors and graded erectile function by using the International Index of Erectile Function (IIEF). The study concluded that the patients had normal erectile hemodynamics, which suggested that their ED could have been psychogenic.…”
Section: Quality Of Life and Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation